Multivalent design of the monoclonal SynO2 antibody improves binding strength to soluble α-Synuclein aggregates - Inga Petersen; Muhammad Ilyas Ali; Alex Petrovic; Anders Jimmy Ytterberg; Karin Staxäng; Monika Hodik; Fadi Rofo; Sina Bondza; Greta Hultqvist (mAbs)
Soluble aggregates are reported to be the most neurotoxic species of α-Synuclein (αSyn) in Parkinson’s disease (PD) and hence are a promising target for diagnosis and treatment of PD. However, the predominantly intracellular location of αSyn limits its accessibility, especially for antibody-based molecules and prompts the need for exceptionally strong soluble αSyn aggregate binders to enhance their sensitivity and efficacy for targeting the extracellular αSyn pool. In this study, we have created the multivalent antibodies TetraSynO2 and HexaSynO2, derived from the αSyn oligomer-specific antibody SynO2, to increase avidity binding to soluble αSyn aggregate species through more binding sites in close proximity. The multivalency was achieved through recombinant fusion of single-chain variable fragments of SynO2 to the antibodies’ original N-termini. Our ELISA results indicated a 20-fold increased binding strength of the multivalent formats to αSyn aggregates, while binding to αSyn monomers and unspecific binding to amyloid β protofibrils remained low. Kinetic analysis using LigandTracer revealed that only 80% of SynO2 bound bivalently to soluble αSyn aggregates, whereas the proportion of TetraSynO2 and HexaSynO2 binding bi- or multivalently to soluble αSyn aggregates was increased to ~ 95% and 100%, respectively. The overall improved binding strength of TetraSynO2 and HexaSynO2 implies great potential for immunotherapeutic and diagnostic applications with targets of limited accessibility, like extracellular αSyn aggregates. The ability of the multivalent antibodies to bind a wider range of αSyn aggregate species, which are not targetable by conventional bivalent antibodies, thus could allow for an earlier and more effective intervention in the progression of PD.